Firm characteristics, corporate governance and value of manufacturing firms: Moderating role of product market competition - Kabir, Musa Usman (2022)
The direct effect of firm characteristics and corporate governance attributes on the value of manufacturing firms in Nigeria was investigated in addition to the moderating effect of product market competition. The metrics of economic value added (EVA) and market value added (MVA) represent the internal and external value which determines the performances of firms from the effect of firm characteristics such as profitability (ROA, ROI), liquidity, capital structure and corporate governance attributes (ownership concentration, managerial ownership, board size). These investigations are premised on the inconclusiveness and the theoretical needs of this study. A balanced panel data of 76 listed Nigerian manufacturing firms for 2012-2016 financial years using the feasible generalised least square (FGLS) was utilised in the analyses. The study indicates the significant positive effect of ROA and ROI on EVA, while only ROI significantly effects MVA. Ownership concentration has a significant positive influence on EVA while ownership concentration, managerial ownership and board size significantly effects MVA. The result also shows that product market competition has a significant positive effect on EVA and MVA. The moderation impact of product market competition on firm characteristics strengthens the influence of profitability and capital structure and reports a significant positive influence of managerial ownership and board size on EVA. The result indicates that the interaction of product market competition strengthens the influence of liquidity, capital structure, ownership concentration and managerial ownership on MVA. The findings also indicate that liquidity, capital structure, managerial ownership and board size weaken EVA, while ROA and capital structure weaken MVA. The moderation of product market competition weakens the effect of ownership concentration on EVA and the effect of ROI and board size on MVA. Thus, this study suggests the continued strengthening of corporate governance practices and the firm characteristics. The findings contribute to signaling, agency and value relevance theories.